DAMPAK CONTENT MARKETING, E-SERVICE QUALITY, DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK BARENBLISS PADA E-COMMERCE SHOPEE DI SIDOARJO - Hidayati, Fitriana Nurul; Sari, Dewi Komala; Hariasih, Misti (Universitas Lancang Kuning, 2024)
The increasing demand for cosmetics and the trend of online shopping through e-commerce have led many cosmetic brands to compete to drive purchasing decisions. This study aims to determine the impact of Content Marketing, E-Service Quality, and Brand Awareness on the Purchase Decisions of Barenbliss Products on E-Commerce Shopee in Sidoarjo. This research uses quantitative methods with the population being people living in Sidoarjo. The sample for this study was taken using Non-Probability Sampling and Purposive Sampling techniques, with a total of 100 respondents living in Sidoarjo who use Barenbliss products and purchase them on E-Commerce Shopee. For data analysis, this study uses multiple linear regression analysis assisted by SPSS Version 26. The results prove that content marketing has a positive and significant impact on purchase decisions, e-service quality has a positive and significant impact on purchase decisions, and brand awareness has a positive and significant impact on purchase decisions.